Correlation Between Leukocyte Differential Counts with The Severity and Outcome of Coronavirus Disease 2019 (COVID-19) Patients In Jember - Angga Mardro Raharjo; Eprila Darma Sari; Diana Chusna Mufida (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Coronavirus Disease 2019 (COVID-19) is an acute respiratory disease caused by new strain of RNA viruses named Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Hematological changes, especially leukocyte differential counts, presumed to be a predictor of the severity and outcome of COVID-19 patients. This study aimed to analyze the correlation between leukocyte differential counts with the severity and outcome of COVID-19 patients. Methods: This study was conducted using a cross-sectional analytic observational method, through secondary data analysis of COVID-19 patients who were tested positive by Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) and hospitalized between April–November 2020 at Citra Husada Jember, Kaliwates Jember, and Jember Klinik Hospital. Results: From 267 patients, there were 139 female patients (52.1%) and 128 male patients (47.9%). There was a positive correlation on leukocytes, neutrophil, and neutrophil-lymphocyte ratio (NLR) with the severity and outcome of the patients, and negative correlation on eosinophils, lymphocytes, and monocytes (P 0.05) Conclusion: Leukocyte differential counts examination could be a predictor of the severity and outcome of COVID-19 patients, especially neutrophils, lymphocytes, and NLR.